Learning Process of Online Class by Using Language Politeness Principles - Daulay, Sholihatul Hamidah; Ningrum, Diah Widya; Nasution, Puspita Sari (Jurnal Ilmiah Peuradeun, 2022)
This article results from research on language politeness in the learning process in the "Language Curriculum Evaluation and Design" class. Leech's politeness principle theory consists of six maxims: tact maxim, generosity maxim, appreciation maxim, modesty maxim, agreement maxim, and sympathy maxim. This study aimed to find out the language politeness used in that class. Then, this study focused on the Lecturer's utterances to the students. The type of this study was descriptive qualitative. The instrument of this study was the researchers themselves and the audio recorder. The technique of collecting the data was tapping techniques to tap the conversation of the Lecturer with the students, field notes and observation. This research showed that Leech's politeness principles were used in that class. The maxim of politeness included tact maxim 22,7%, generosity maxim 13,6%, appreciation maxim 18,2%, modesty maxim 9,1%, agreement maxim 18,2%, and sympathy maxim 18,2%. Most of the maxims used in that class are tact maxims. After analyzing these six maxims, it is essential to have them when we are a lecturer teaching in the class. A teacher with the six maxims can control the class to run well.